Student veterans’ construction and enactment of resilience: A constructivist grounded theory study - Reyes, A. T.; Kearney, C. A.; Isla, K.; Bryant, R. (Journal of psychiatric and mental health nursing, 2018)
Accessible summary What is known on the subject? Resilience is an ability and a process that allows an individual to develop positive adaptation despite challenges and adversities. Many military veterans returning to college after their military service have difficulty transitioning to civilian life. Although some research exists that explores factors related to the resilience of college student veterans, limited theoretical descriptions exist that explain how student veterans construct resilience, and how resilience is enacted and enhanced in their academic and personal (non‐academic) lives. What this paper adds to existing knowledge? The resilience of student veterans involves a complex process of transitioning from military to civilian life and an iterative journey between positive adaptation and transient perturbations. Student veterans’ resilience is a result of integrating and resolving various aspects of their academic and personal challenges. What are the implications for practice? Nurses can apply this grounded theory as a practical framework for equipping student veterans with effective strategies to develop and enhance resilience. Nurses can employ a holistic approach of care in their interactions with military veterans and student veterans that includes fostering psychological resilience, helping to manage their multiple non‐academic responsibilities and supporting their academic success. Introduction Adjusting to college life is one of the most difficult experiences in a military veteran's transition to civilian life. Many military veterans returning to college not only encounter academic challenges, but also deal with physical and psychiatric disabilities, loss of military camaraderie and social disconnect. These often negatively affect their personal and academic lives. Hence, it is important to explore resilience to best support student veterans as they transition from military to civilian life. Aim The aim of this study was to explore how student veterans construct and enact resilience within their personal and academic lives. Method Using constructivist grounded theory methodology, in‐depth individual interviews were conducted with 20 military veterans enrolled as undergraduate students at a U.S. university. Results The process of “integrating,” which represents student veterans’ construction and enactment of resilience, was the core category. This category has three subcategories: (1) the aspects; (2) the expressions; and (3) the enactments of resilience. Implications for practice Nurses can use this grounded theory as the practical framework for their interactions with military veterans, and more particularly with supporting student veterans in their academic lives, in their personal lives and in the transition from military to civilian life.